Quality of life in menopausal women attending gynaecology OPD in a tertiary care hospital - Agrawal, Deepika; Sharma, Manisha; Popli, Sangeeta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: The longevity of women due to increase in life expectancy makes them spend almost one third of life after menopause. Menopause is a transitional event that can profoundly affect quality of life. It is an adaptation process accompanied by many biological, psychological changes. Aim of the study was to study menopause related symptoms, their severity and impact on quality of life. Methods: The longevity of women due to increase in life expectancy makes them spend almost one third of life after menopause. Menopause is a transitional event that can profoundly affect quality of life. It is an adaptation process accompanied by many biological, psychological changes. Aim of the study was to study menopause related symptoms, their severity and impact on quality of life. Results: The present study showed that the most severe symptoms of vasomotor, psychological, physical and sexual domains were hot flushes, night sweats, feeling of wanting to be alone, feeling depressed, low backache, change in sexual desire. In group 1 there were more vasomotor symptoms as compared to group 2. Severity of psychological, physical, sexual symptoms increased in group 2. In local gynaecological examination more abnormalities were found in group 2 (34%) as compared to group 1 (14%). Also, there was an increased percentage of diabetes (18.96%), hypercholesterolemia (31.03%), hypertriglyceridemia (31.03%) in group 2. Conclusions: Our study concluded that by identifying characteristics associated with poor quality of life of menopausal women would help them in making strategies that are required for improving their health and quality of life.